O gerenciamento de resíduos sólidos como instrumento de gestão ambiental em empresas - Ferreira, Maria Adélia Vasconcelos (2012)
This study aims to assess the importance of managing solid waste in a company with ISO 14001 certification and has Coelce’s administrative headquarters as object of study. It was, used a qualitative exploratory and methodology in order to understand the solid waste management process developed to assess the perceptions of employees regarding the management of solid waste held in the company and view the practices adopted to maintain such management. The results makes us understand that, despite a solid waste management structured, with close monitoring of waste which meets all legal requirements, the company said forwards organic waste to landfill, which indicates the need for a destination that requires a minimum waste disposal to the environment. You can also see, through questionnaires and informal interviews, which company officials have studied knowledge of procedures and practices necessary for solid waste management adopted by the Company by employees, but most do not put it into practice by indifference, making it necessary to adopt measures to reverse this situation. Finally, we conclude that the participation and interest of employees and the organization itself are critical to the success of a waste management as a tool to ensure the effectiveness of an environmental management system.